Оценка условий труда некоторых профессий железнодорожных предприятий - Аманжол, И.А.; Жарылкасын, Ж.Ж.; Отаров, Е.Ж. (Актуальні проблеми транспортної медицини, 2005)
The aim of the work presented is to estimate labour condition of a rail-way enterprise workers. There were 138 persons under examinations, they all worked in the Jairem mining enterprise (Central Kazakhstan). The representatives of the following professional groups have been under investigation: the locomotive - drivers, drivers assistants, train compilers, boiler operators, baggage operators, etc. As a rule, labour condition at the working places mentioned above have been kept in accordance with sanitary - and - hygienic requirements. The working places of locomotive - drivers assistants were characterized by high degree of dust content in the air of the working zone, conformable to the 1st class of occupational risk.